Direct Selling For Dummies - Ellsworth, Belinda (Tantor Media, Inc., 2019)
Direct Selling For Dummies is the perfect resource for anyone involved or interested in direct sales. Written by a thirty-five-year veteran of this booming industry, this useful guide teaches you everything you need to know to achieve and maintain lasting success. You'll learn the insider tips that only the pros know, and how to structure your business, your time, and your customer relationships to optimize sales and achieve your goals. Compare party plans, multi-level marketing, and hybrid models to see where your talents fit best, and discover the most effective ways to promote your products and get people interested. You'll leverage social media as one of the most powerful tools in modern sales, and gain new ideas for recruiting, booking, and time management. With clear guidance and a fun, friendly style, this book gives you the strategies you need to be a direct sales success. The direct sales industry is going strong, with more participants now than any time in the past, yet with less face-to-face engagement. Businesses are operating online, people are shopping online, and more people are recruiting through platforms like social media. If you hope to be a direct sales success, now is the time to get up to speed on what that means today. This book shows you everything you need to know, and gives you the tools you need to put your ideas into action.